Use of Interactive Methods to Familiarize Students with Place Names Given in The Elementary Science Program (Open Academia: Journal of Scholarly Research, 2024)
This article explores the efficacy of interactive methods in acquainting elementary students with place names featured in the science curriculum. Utilizing engaging activities and technology, such as virtual maps, quizzes, and interactive games, this study investigates the impact of interactive learning on enhancing students' geographical knowledge. Through a mixed-method approach, incorporating pre- and post-assessments alongside qualitative observations, the research assesses the effectiveness of interactive methods in fostering place name recognition among elementary students. Findings suggest that interactive techniques significantly improve students' retention and understanding of place names, thereby enhancing their overall learning experience in science education